Intelligent street lighting application for electric power distribution systems the business case for smartgrid technology - Davis, Wesley O'Brian Sr. (Kansas State University, 2011)
This research project builds upon previous work related to intelligent and energy efficient lighting in modern street and outdoor lighting systems. The concept of implementing modern smart grid technologies such as the proposed Street & Outdoor Lighting Intelligent Monitoring System (SOLIMS) is developed. A random sample of photocells from two municipal electric power systems is used to collect data of the actual on/off times of random photocells versus Civil Twilight (sunrise/sunset) times. A business case was developed using the data collected from the observations to support an electric utility company’s implementation of SOLIMS as an alternative to current operations. The goal of the business case is to demonstrate energy and capacity savings, reduced maintenance and operating costs, and lower carbon emissions.
Keywords: Street lighting; Smart-Grid; Electrical Engineering (0544)